Perancangan Interior Tourism Activity Center di Banyuwangi - Sylvia Agustin Irawan (Intra, 2017)
is a city in East Java that has abundant of nature, culture, and attractions that continue to grow. Its location close to the island of Bali makes Banyuwangi become a liaison path that many tourists pass by. With this potential, its increase the tourism sector in Banyuwangi, that can be an important factor to support its progress. Many potentials are being developed by the local government to continue to improve the city of Banyuwangi, especially the potential of culture and tourism.Designing Tourism Activity Center has two main objectives as a means of education and socialization. The purpose of education is to accommodate the activities of tourists visiting the city of Banyuwangi in order to know the local culture. While the social objective is to facilitate the activities of art festivals held by the Local Government and develop the livelihood of the people of Banyuwangi through workshops or exhibitions. The design uses design thinking method based on theory by Gavin Ambrose and Paul Harris, consist of: define, research, ideate, prototype, select, implement, learn Implementation design using the concept from The Art of Exploring that apply in the local culture art of Banyuwangi into its design. Where in the process of exploring visitors can enjoy the atmosphere presented and provide its own experience through cultural elements in space.